User Evaluation of the Bibit Reksadana Application using the User Experience Questionnaire (UEQ) of Semarang Regency - pratama, raihan daffa arya; Tanaamah, Andeka Rocky (Sistemasi: Jurnal Sistem Informasi, 2025)
According to data from the Indonesian Central Securities Depository (KSEI), by the end of 2023, the Bibit mutual fund application had reached 4.6 million users. This phenomenon has generated diverse responses from the public, particularly between novice and experienced investors. This study aims to evaluate the user experience of the Bibit application using the User Experience Questionnaire (UEQ) method. Data was collected through questionnaires distributed using purposive sampling, targeting individuals who actively use the application. The evaluation focuses on six UEQ aspects: attractiveness, clarity, efficiency, dependability, stimulation, and novelty, analyzed using the Data Analysis Tools developed by the UEQ team. The findings reveal variations in user experience, providing insights into both user satisfaction and challenges encountered. Overall, this study offers valuable insights into the user experience of the Bibit application and highlights areas for improvement, which can be leveraged to enhance the quality of the app’s services in the future.